Denosumab treated giant cell tumour of bone: a morphological, immunohistochemical and molecular analysis of a series. Issue 3 (3rd September 2015) - Girolami, Ilaria; Mancini, Irene; Simoni, Antonella; Baldi, Giacomo Giulio; Simi, Lisa; Campanacci, Domenico; Beltrami, Giovanni; Scoccianti, Guido; D'Arienzo, Antonio; Capanna, Rodolfo; Franchi, Alessandro
Abstract : Aims: Denosumab, a fully human monoclonal antibody directed against RANKL, has recently been introduced in the treatment strategy of giant cell tumour of bone (GCTB). Aim of this study was to investigate the phenotypical modifications induced by denosumab treatment in a series of 15 GCTB. Methods: The tumours were characterised for histone 3.3 mutations, and studied immunohistochemically for the modifications of RANKL, RANK, SATB2 and RUNX2 expression, as well as of tumour proliferative activity and angiogenesis. Results: Nine of 11 tumours investigated presented a histone 3.3 mutation in H3F3A, and 2 of these for which the analysis was carried out in pretreatment and post-treatment specimens showed the same mutation in both. Denosumab induced the disappearance of osteoclast-like giant cells, leaving residual spindle neoplastic cells arranged in a storiform pattern, with deposition of trabecular collagen matrix and osteoid, which tended to maturation in the peripheral portions of the lesion. RANK and RANKL expression was variable, with no significant variation after treatment. Moreover, we did not observe any significant modification of the expression of the osteoblastic markers SATB2 and RUNX2. Denosumab treatment determined a significant reduction of the proliferative index and of tumour angiogenesis (p=0.001, Wilcoxon rank-sum test). Conclusions: These results indicate that denosumab induces a partial maturation towards the osteoblastic phenotype of the neoplastic cells of GCTB, with production of fibrous and osteoid matrix, but with minor immunophenotypical changes. Finally, we first report an antiangiogenic activity of denosumab in GCTB, possibly mediated by a RANKL-dependent pathway.